Turkish soaps: understanding pleasure among Iranians and the underlying political economy - Matin, Alireza Azeri (Penerbit Universiti Kebangsaan Malaysia, 2021)
This article examines how young urban audiences in Iran derive pleasure from transnationally broadcasted Turkish soaps. Since the early 1990s, the furtherance of developments in communication technologies and the emergence of the new forces in the global television market have resulted in a profusion of free-to-air satellite TV programmes, transforming the television in Iranians' living rooms from a local and monotonous medium into a vibrant and abundant one. Flooded with a cornucopia of tele-viewing choices, Iranian audiences have particularly been enthralled by Turkish soap operas in recent years. Such popularity, especially among younger audiences, is remarkable considering the general prohibition of satellite TV in Iran and authorities' specific censure of Turkish soaps for having corrupting effects on Iranian culture. While soaps have historically been regarded as pleasurable texts primarily aimed towards women, the consumption of non-local forms of such popular cultural programmes both by male and female Iranian audiences raises questions about the kind of pleasures derived according to their gender-specificity. Through an analysis of the data drawn from a series of focus group discussions with 25-35 years old participants in Tehran, this study explores the diverse ways in which these individuals derive pleasure from watching Turkish soaps. Ultimately, the findings challenge the extrapolation of the traditional theories of political economy, which regards Turkish soaps as global purveyors of predetermined pleasure circumscribed by forces of international markets, and instead suggests that the kinds of pleasure can only be ascertained at the local level of consumption.